Relationship between SGLT2 inhibitor use and risk of lower limb amputations: a pharmacovigilance study - Khandker, Tahia Anjum (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.